2019
DOI: 10.48550/arxiv.1901.01663
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On Global-in-Time Strichartz Estimates for the Semiperiodic Schrödinger Equation

Alexander Barron

Abstract: We prove global-in-time Strichartz-type estimates for the Schrödinger equation on manifolds of the form R n × T d , where T d is a d-dimensional torus. Our results generalize and improve a global space-time estimate for the Schrödinger equation on R × T 2 due to Z. Hani and B. Pausader. As a consequence we prove global existence and scattering in H 1 2 for small initial data for the quintic NLS on R × T and the cubic NLS on R 2 × T.with optimal scaling for p near the Stein-Tomas endpoint in dimension n + d. No… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…For waveguide case, we recall the Strichartz estimate (local-in-time version) proved by Barron [1] as follows. The proof of Theorem 3.2 is based on the decoupling method established in Bourgain-Demeter [4].…”
Section: Overview Of Strichartz Estimate For Waveguide Manifoldmentioning
confidence: 99%
See 1 more Smart Citation
“…For waveguide case, we recall the Strichartz estimate (local-in-time version) proved by Barron [1] as follows. The proof of Theorem 3.2 is based on the decoupling method established in Bourgain-Demeter [4].…”
Section: Overview Of Strichartz Estimate For Waveguide Manifoldmentioning
confidence: 99%
“…Please see [19,20,22,23,29,34,35,36] for more information. The main purpose of this paper is to give a unified and simpler treatment of well-posedness results based on the Strichartz estimate established in Barron [1].…”
Section: Introductionmentioning
confidence: 99%
“…Remark 1.3. It's expected that Theorem 1.1 holds for s > 1 2 since (1.1) is "H 1 2critical". Other methods or delicate techniques are required for one to obtain the sharp result.…”
Section: Introductionmentioning
confidence: 99%
“…the Strichartz estimate and the bilinear estimate in the waveguide setting is as same as in the tori setting. (See Barron [1] and Section 3 of this paper respectively.) Thus, in our previous result [12], we showed that we only need to care about the whole dimension of the waveguide, not the distribution of the Euclidean dimensions and the tori dimensions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation